Argumentative communication in cooperative learning groups: Members' use of evidence and non-evidence. Issue 1 (2nd January 2020) - LeFebvre, Leah E.; Yilmaz, Gamze; LeFebvre, Luke; Allen, Mike
ABSTRACT: This study examined how group members with differential levels (highest, middle, and lowest) of ability contributed to argumentative communication while facilitating a cooperative learning process in a small group communication course. Results demonstrated that during discussions: (1) highest ability members utilized more evidence than middle or lowest ability members, (2) lowest ability members generated more non-evidence than evidence, and (3) middle ability members appeared to be less active in articulating evidence. These findings provide evidence that instructors should focus on teaching students how to communicate evidence, identify facilitative versus inhibitive arguments, and respectfully acknowledge and evaluate contributions for effective group learning.